HEPATORENAL SYNDROME WITH ACUTE RENAL FAILURE IN PATIENTS WITH CHRONIC LIVER DISEASE: MODERN ASPECTS OF CLINICAL PRESENTATION AND INTENSIVE CARE - R. R. Nagimullin; F. A. Shipulin; A. Zh. Bayalieva (Креативная хирургия и онкология)
Introduction. Acute renal failure is considered a functional, progressive, oliguric, but reversible kidney disease that occurs due to severe liver disease with hepatic insufficiency. In the development of the syndrome, the leading role is played by the “classical hypothesis of peripheral vasodilation”. Important differentiation in verification of diagnosis is primarily with pseudo hepatorenal syndrome. In the type I (of hepatorenal syndrome) mortality in the first 10 days without an adequate management in intensive care unit is extremely high. The chronic, type II, is a slow process, but requires adequate therapy for up to six months. In general, all clinical manifestations of hepatorenal syndrome are combined into three groups: cardiac insufficiency, systemic vasodilation, and vasoconstriction of renal vessels. The goals of the therapy include restoration of blood flow through the vessels, management of inflammatory processes, prevention of further hepatic tissue destruction, and stabilization of arterial blood pressure in kidney vessels. The core in medical management is adequate albumin infusion and minimal crystalloid support of blood volume, vasopressors, adequate antidote and antibacterial therapy. Additional methods include extracorporeal albumin dialysis to bridge patient to liver transplantation. The orthotopic liver transplantation is the established surgical treatment, as well as transjugular intrahepatic portosystemic shunt (TIPS) or peritoneovenous shunt. Survival rate of patients with hepatorenal syndrome type I on terlipressin in patients with hypoalbuminemia correction is close to 60–75%; survival of with hepatorenal syndrome type II is more favorable in most cases.Methods. The literature review examines diagnostics possibilities of hepatorenal syndrome, importance of timely relevant differential diagnoses and adequate intensive care management.Conclusion. The differential diagnosis between hepatorenal syndrome and pseudo hepatorenal syndrome remains a challenge in routine diagnostic examinations. Intensive care management of such patients requires immediate treatment, which may not be always the most appropriate option. The refore new strategies are needed to improve management of this medical condition.